Oral health‐related quality of life among young adults with cleft in northern Finland - Corcoran, M. (Mirjami); Karki, S. (Saujanya); Harila, V. (Virpi); Kyngäs, H. (Helvi); Luoto, A. (Anni); Ylikontiola, L. P. (Leena P.); Sándor, G. K. (George K.); Anttonen, V. (Vuokko) (John Wiley & Sons, 2020)
Abstract Objectives: This study aimed to examine Oral Health‐related Quality of Life (OHRQoL) among patients with cleft lip with or without palate (CLP) at their final scheduled follow‐up visit at the age of 18 years. Another aim was to investigate the motivation to attend multiple follow‐up appointments and the satisfaction with care given by the cleft team using inductive qualitative analysis. Methods: This cross‐sectional study was conducted among the cohort of children born with CLP who had undergone treatment at the Oulu University Hospital Cleft Lip and Palate Centre, in northern Finland since 1995. OHRQoL was assessed using the validated Finnish version of the short form of the Oral Health Impact Profile (OHIP‐14). In addition to the OHIP‐14, two open‐ended questions were also included. These questions investigated the experience of each participant concerning their motivation to attend the Oulu University Hospital Cleft Lip and Palate Centre to receive complex treatments, and their satisfaction with care provided by the cleft team. Results were presented as proportions, means, and SD. Inductive content analysis method was performed for analysis of the open‐ended questions. Results: A total of 63 patients with CLP participated in this study. More than half of the participants had cleft palate. More than half of the participants reported an impact on OHRQoL (OHIP‐14 score ≥ 3). All the participants with bilateral cleft lip and palate, three fourths of the participants with unilateral cleft lip and palate, and half of the participants with cleft palate reported impact on OHRQoL. Inductive content analysis showed that one fourth of the participants reported a good outcome as a motivation to attend cleft center despite of complex procedures. All the participants reported their appreciation of the cleft team. Conclusions: Despite the comprehensive treatment received by the patients born with a CLP, they still experienced lower OHRQoL, especially physical pain and psychological discomfort were more pronounced. ...